Appraisal in Threads: Digital Persona Construction of Indonesian Fitness Influencers - Hestika Ginting; Winaria Peggy L. Simanjuntak (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
This study explores how Indonesian fitness influencers create digital personas using evaluative language on Threads by drawing upon Martin and White’s (2005) Appraisal framework comprised of Attitude, Engagement and Graduation. Following a qualitative netnographic approach (Kozinets, 2015), data was collected from six selected influencer posts based on their activity and relevance to fitness-oriented discourse. Findings reveal that Attitude (Affect) is the most prominent resource, emphasizing emotional expression as key to establishing relatability and engagement, while Judgement and Appreciation reinforce fitness discipline and its worth. Engagement leans towards authoritative positioning, tempered by inclusivity to align audiences, and Graduation strengthens evaluative meanings for more impactful persuasion. These patterns produce three dominant digital personas, namely Motivator, Coach, and Companion, showing how evaluation serves as a strategic device for identity enactment and audience engagement in digital communication.